Solid-Phase Synthesis and Fluorine-18 Radiolabeling of CycloRGDyK - Davis, Ryan A. (Org Biomol Chem, 2016)
Solid-phase peptide synthesis, head-to-tail cyclization, and subsequent radiolabeling provided a reproducible, simple, rapid synthetic method to generate the cyclic peptide radiotracer cRGDyK([(18)F]FBA). Herein is reported the first on-resin cyclization and (18)F-radiolabeling of a cyclic peptide (cRGDyK) in an overall peptide synthesis yield of 88% (cRGDyK(NH(2))) and subsequent radiolabeling yield of 14 ± 2% (decay corrected, n = 4). This approach is generally applicable to the development of an automated process for the synthesis of cyclic radiolabeled peptides for positron emission tomography (PET).